2019
DOI: 10.2298/jsc190227021b
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the thermostable alkaline and Ca-dependent α−amylase production from Bacillus paralicheniformis by statistical modeling

Abstract: A novel amylolytic enzyme producing thermoalkaliphilic bacterium, the source of industrially used enzymes was isolated. Isolated strain was identified by morphological, physio-biochemical tests and the 16S rRNA gene sequence analysis. The optimal conditions of enzyme activity were determined. For higher α-amylase production, the variables such as yeast extract, starch, CaCl 2 , (NH 4) 2 SO 4 , NaCl and MgSO 4 in the α-amylase production medium, the temperature and pH were screened by Plackett-Burman design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…While for α-amylase production only 7 variables exerted a significant effect on enzyme production distinguished into 5 positive variables that exerted enhancement effect (RS weight, (NH 4 ) 2 SO 4, CaCl 2 , baker's yeast, and PS weight) and 2 negative variables (lactose, and CuSO 4 ). The enhancement effect of CaCl 2 on α-amylase production was also reported by Balkan et al (2011) andBekler et al (2019). While, Retnaningrum & Purwestri (2016) and Hazaa et al (2018) found α-amylase production was enhanced by the addition of, starch and yeast extract as carbon and nitrogen sources, maltose followed by lactose, respectively.…”
Section: Statistical Optimization Of Splicatus Mk559563 Xylanase and α-Amylase Production Plackett-burman Design (Pb)supporting
confidence: 65%
“…While for α-amylase production only 7 variables exerted a significant effect on enzyme production distinguished into 5 positive variables that exerted enhancement effect (RS weight, (NH 4 ) 2 SO 4, CaCl 2 , baker's yeast, and PS weight) and 2 negative variables (lactose, and CuSO 4 ). The enhancement effect of CaCl 2 on α-amylase production was also reported by Balkan et al (2011) andBekler et al (2019). While, Retnaningrum & Purwestri (2016) and Hazaa et al (2018) found α-amylase production was enhanced by the addition of, starch and yeast extract as carbon and nitrogen sources, maltose followed by lactose, respectively.…”
Section: Statistical Optimization Of Splicatus Mk559563 Xylanase and α-Amylase Production Plackett-burman Design (Pb)supporting
confidence: 65%
“…Likewise, the producing strain enhances its enzyme synthesis depending on its phase of growth (lag, exponential, etc.) 24 and for this reason, there is an optimum cultivation time when the enzyme activity is at its top. Finally, if the lines of two parameters intersect twice at different point of the observed interval, these two parameters have a joint influence on the response.…”
Section: Optimization Of the Process Parametersmentioning
confidence: 99%
“…RSII-1b and Bacillus tequilensis RG-01, respectively. However, other studies reported the production of amylases at a wider range of temperatures as mentioned and reported by Bekler et al who obtained the maximum level of amylase from Bacillus paralicheniformis at 60°C [ 13 ].…”
Section: Discussionmentioning
confidence: 98%
“…Statistical and mathematical techniques for predicting the behavior of process variables and explaining their interactions, and response surface methodology (RSM) have been applied in the optimization of amylase production [11][12][13].…”
Section: Introductionmentioning
confidence: 99%